Recycled Concrete Aggregated for the use in Roller Compacted Concrete: A Literature Review (Journal of Engineering, 2023)
The using of recycled aggregates from construction and demolition waste (CDW) can preserve natural aggregate resources, reduce the demand for landfill, and contribute to a sustainable built environment. Concrete demolition waste has been proven to be an excellent source of aggregates for new concrete production. At a technical, economic, and environmental level, roller compacted concrete (RCC) applications benefit various civil construction projects. Roller Compacted Concrete (RCC) is a homogenous mixture that is best described as a zero-slump concrete placed with compacting equipment, uses in storage areas, dams, and most often as a basis for rigid pavements. The mix must be sufficiently dry to support the weight of vibratory machinery while still being sufficiently moist to enough paste binder dispersion throughout the mass for efficient compaction. Limited studies into the use of RCC with fine recycled aggregate not from pavements are figured. This study aims to see how well-recycled concrete aggregates (RCA) perform in RCC mixtures. Also how well waste concrete could be used as a fine and coarse aggregate substitute in roller-compacted concrete pavement mixes, to create a good concrete mix in both wet and firm phases. The test results of mechanical properties showed 10% RCA is similar to those in the reference mix in the compressive strength, a 100% RCA ratio reduces compressive strength by almost 30%. Comparing Reference mix and Recycled concrete by 30% replacement, the compressive strength drops by just 6% when the RCA ratio is 30%.